PENGUASAAN TECHNOLOGICAL PEDAGOGICAL AND CONTENT KNOWLEDGE (TPACK) MAHASISWA - Amalia, Lutvi (Titik Fokus Karya, 2023)
Technological Pedagogical and Content Knowledge (TPACK) is a combined conceptual framework of interrelated knowledge of content, pedagogy, and technology that aims to make learning more effective and efficient. To improve learning activities, teachers must have knowledge so that teachers can integrate technology into learning as well as possible, including prospective teachers. PGMI is one of the majors that produces prospective teachers in basic education, so mastery of TPACK is important for PGMI students as prospective teachers before they become educators. The purpose of this study was to determine the TPACK mastery of PGMI UIN Antasari students and to determine the level of TPACK mastery of PGMI UIN Antasari students. The number of respondents in this study was 10 people. This type of research is quantitative research with a descriptive approach using survey methods. The sampling technique uses the slovin formula. Data collection techniques using questionnaires or questionnaires. The data analysis technique used is descriptive statistical analysis. The results showed that the TPACK mastery of PGMI UIN Antasari students was Medium and Low. Mastery of TPACK in the medium category, namely Technological Knowledge and Technological Pedagogical Knowledge. And the mastery of TPACK is in the low category, namely Pedagogical Knowledge, Content Knowledge, Pedagogical Content Knowledge and Technological Content Knowledge. The level of mastery of TPACK in the medium category is TK (3.40) and TPK (3.21) in the low category PK (2.93), CK (2.80), PCK (2.97), TCK (2.86).